A Database of Wing Diversity in the Hawaiian Drosophila - Edwards, Kevin A. (Public Library of Science, 2007)

(untitled)
BACKGROUND: Within genus Drosophila, the endemic Hawaiian species offer some of the most dramatic examples of morphological and behavioral evolution. The advent of the Drosophila grimshawi genome sequence permits genes of interest to be readily cloned from any of the hundreds of species of Hawaiian Drosophila, offering a powerful comparative approach to defining molecular mechanisms of species evolution. A key step in this process is to survey the Hawaiian flies for characters whose variation can be associated with specific candidate genes. The wings provide an attractive target for such studies: Wings are essentially two dimensional, and genes controlling wing shape, vein specification, pigment production, and pigment pattern evolution have all been identified in Drosophila. METHODOLOGY/PRINCIPAL FINDINGS: We present a photographic database of over 180 mounted, adult wings from 73 species of Hawaiian Drosophila. The image collection, available at FlyBase.org, includes 53 of the 112 known species of “picture wing” Drosophila, and several species from each of the other major Hawaiian groups, including the modified mouthparts, modified tarsus, antopocerus, and haleakalae (fungus feeder) groups. Direct image comparisons show that major wing shape changes can occur even between closely related species, and that pigment pattern elements can vary independently of each other. Among the 30 species closest to grimshawi, diverse visual effects are achieved by altering a basic pattern of seven wing spots. Finally, we document major pattern variations within species, which appear to result from reduced diffusion of pigment precursors through the wing blade. CONCLUSIONS/SIGNIFICANCE: The database highlights the striking variation in size, shape, venation, and pigmentation in Hawaiian Drosophila, despite their generally low levels of DNA sequence divergence. In several independent lineages, highly complex patterns are derived from simple ones. These lineages offer a promising model system to study the evolution of complexity.